Alpha–proton relative drift: implications for the origins and dynamics of the solar wind - Wang,JH; Horbury,TS; Matteini,L; Trotta,D (Letters of the Astrophysical Journal, 2025)
Helium nuclei (alpha particles) strongly influence the momentum and energy balance in the solar wind, comprising up to 20% of the solar wind mass density. In fast Alfvénic wind at heliocentric distances greater than 0.3 au, the alpha particles' bulk flow speed is systematically different to that of the protons. This relative drift speed is of unknown origin and is often close to the local Alfvén wave speed. Novel Parker Solar Probe measurements of the solar wind below 0.3 au show that, closer to the Sun, the alpha–proton drift speed remains on the order of 100–200 km s−1, even where the Alfvén speed is greater than 600 km s−1. This relative speed is quantitatively similar to oxygen–hydrogen drift speeds observed in the transition region by remote sensing, suggesting similar selective acceleration processes in the corona. Due to the relative speed of the Alfvén wave to each particle population close to the Sun, the alphas fluctuate with velocity amplitudes comparable to those of the protons, altering the energy balance of the wave. As a result, alpha particles carry a significant fraction of the total kinetic energy in Alfvénic fluctuations in the near-Sun solar wind. The alpha–proton drift speed is comparable to the proton speed in the near-Sun wind, making the bulk flow of the alpha particles a significant contribution to the kinetic energy flux. These heavy-ion dynamics provide new observational constraints on quantifying the energy budget of the solar wind and the magnetic field evolution through the heliosphere.